PENGARUH UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP NILAI PERUSAHAAN MELALUI PRAKTEK MANAJEMEN LABA RILL - Rezki Zurriah; Masta Sembiring (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2020)
The objective of the research was to analyze the influence of the firm size, and leverage on firm value through the practice of rael earnings management in companies listed in the Jakarta Islamic Index in the period of 2015-2018. The samples were 18 companies, taken by using purposive sampling technique with the total observation of 54 analytical units. Secondary data were gathered by conducting documentary study like annual financial statement publicized in Indonesian Stock Exchange. The gathered data were analyzed by using multiple linear regression analysis and path analysis. The result of the research showed that firm size and leverage simultaneously had significant influence on the value of companies listed in the Jakarta Islamic Index. Partially, leverage did not have any significant influence on firm value, while firm size had positive and significant influence on firm value. Based on the result of Sobel test on the variables of firm size, it was found that real earnings management did not act as intervening variable, while the result of Sobel test on the variable of leverage showed that real earnings management acted as intervening variable.